Spatial Environmental Quality Assessment Of Settlement Area In Tangerang City - Dwi Nowo Martono; Halvina Grasela Saiya; Saiful Amri (Faculty of Geography, Universitas Gadjah Mada, 2022)
This study aims to describe the role of changes in the characteristics of spatial patterns on the environmental quality in Tangerang City, Indonesia. It was carried out by detecting and explaining the effect of thermal comfort on the residential area using a combination of spatial and statistical analysis methods. The results showed that the changes in the characteristics of the spatial pattern, which include building density, vegetation area, accessibility, and road network connectivity significantly affected the spatial environmental quality index (IKLS) and temperature heat index (THI). Meanwhile, the changes in THI were caused by the continuous decline in vegetation area and an increase in population due to the urbanization process of Jakarta and other cities.